To Determine the Efficacy of Antibiotic Prophylaxis in patients Undergoing Flexible Cystoscopy - Umer Javed Chughtai, Rameez Ahmed, Umar Hussain, Bilal Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Flexible cystoscopy is a commonly performed intervention in urology practice. It has both diagnostic and therapeutic value and has an added advantage of being used as an outpatient procedure. However one of the common complication associated with it, is the development of Urinary tract infection (UTI) because of its minimally invasive nature. Aim: To determine the efficacy of antibiotic prophylaxis in patients undergoing flexible cystoscopy. Methods: A randomized control study was performed in total 144 patients selected for flexible cystoscopy. Patients were divided into Group A (Antibiotic group) and Control Group B. Group A received a single dose of Levofloxacin 500mg one hour before procedure, while no antibiotic prophylaxis was given to Group B. Primary outcome was development of UTI, which was assessed by subjective symptoms of UTI, results of urine culture and routine urine examination at 1st week after the procedure Results: After 1 week of procedure, 5 patients (6.9%) in Group A and 7 patients (9.7%) in Group B developed UTI. 3 patients (4.1%) in Group A and 6 patients (8.3%) in Group B developed asymptomatic bacteriuria after 1 week. 64 patients (88.9%) in Group A and 59 patients (81.9%) in Group B did not develop UTI after 1 week of procedure Conclusion: Prophylactic use of antibiotics before flexible cystoscopy has no effect in reducing the frequency of post procedure urinary tract infections Keywords: Urinary Tract Infection UTI), Cystoscopy, Antibiotic prophylaxis